Cardiac benefits of exercise training in aging spontaneously hypertensive rats - Rossoni, Luciana V.; Oliveira, Raphael A. F.; Caffaro, Rene R.; Miana, Maria; Sanz-Rosa, David; Koike, Marcia K.; Do Amaral, Sandra L. [UNESP]; Michelini, Lisete C.; Lahera, Vicente; Cachofeiro, Victoria (Lippincott Williams & Wilkins, 2011)
Objective To evaluate the effect of low-intensity chronic exercise training (ExT) on blood pressure (BP), as well as the cardiac alterations associated with hypertension in aging hypertensive rats.Methods Male spontaneously hypertensive rats (SHR; 21 months old) and their normotensive control Wistar-Kyoto (WKY) rats were submitted to low-intensity training protocol for 13 weeks. BP, cardiac morphological and morphometric analysis, as well as gene expression of fibrotic and inflammatory factors were analyzed at the end of the training period.Results ExT reduced BP and heart rate in aged SHR. Left ventricle hypertrophy, collagen volume fraction and wall-to-lumen ratio of myocardium arterioles were also decreased in trained SHR. However, ExT was unable to reverse the either reduced capillary density or the cardiac myocyte hypertrophy observed in SHR as compared with WKY rats. Trained SHR showed higher metalloproteinase-2/tissue inhibitor metalloproteinase-2 (MMP-2/TIMP-2) ratio and lower levels of a-smooth muscle actin, but similar levels of connective tissue growth factor, transforming growth factor beta or IL-1 beta to that of nontrained SHR.Conclusion Low to moderate-intensity chronic ExT reverses the cardiac alterations associated with hypertension: myocardial arteriole, left ventricle hypertrophy, collagen content and tachycardia. These changes could be consequence or cause of the reduction in BP observed in trained SHR. In addition, ExT does not worsen the underlying inflammatory burden associated with hypertension. Therefore, the data support a beneficial effect of ExT in aging SHR similar to that reported in young or middle-aged individuals, confirming that exercise is a healthy habit that induces cardiac improvements independently of age. J Hypertens 29: 2349-2358 (C) 2011 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.
Keywords: collagen content; exercise training; hypertension; left ventricle hypertrophy; spontaneously hypertensive rats; vascular remodeling